Impacts of COVID-19 pandemic on the collection and use of blood and blood components in Taiwan - Ling-I Hsu; Jen-Wei Chen; Sheng-Tang Wei; Sheng-Mou Hou (Journal of the Formosan Medical Association)
Background: The coronavirus disease 2019 (COVID-19) pandemic has significantly impacted the supply and transfusion of blood components. This study aims to evaluate changes in blood collection and transfusions during the period following the nationwide Level 3 alert (May–July 2021). Methods: We retrieved usage data for red blood cells (RBC) from the Taiwan National Health Insurance (NHI) database 2019–2021. Results: During the Level 3 alert period, approximately 85% of COVID-19 cases (11,455/13,624) were in Taipei. In Taipei, blood collection declined by 26.34% and RBC transfusions decreased by 17.14% compared to pre-pandemic levels. RBC usage decreased across all service types, with a significant decrease observed in hematology/oncology by 15.62% (-483 patients, -2,425 units). In non-Taipei regions, blood collection declined by 12.54%, rebounding around one month earlier than in Taipei. The decline in RBC transfusions occurred one month later than in Taipei, with a much lower magnitude (4.57%). Strain on the blood supply occurred in May and June in both Taipei and non-Taipei regions. Among 7,532 hospitalized COVID-19 patients, approximately 6.9% patients required a total of 1,873 RBC transfusions. The rapid increase in COVID-19 inpatients did not significantly increase the burden of blood demands. Conclusion: During the Level 3 alert, the most significant decline in both RBC collection and transfusions was observed in Taipei. In non-Taipei regions, the decrease in RBC use was only marginal. Notably, there was a significant decrease in RBC use in hematology/oncology in Taipei. This study supports transfusion specialists in seeking efficient ways to address similar future challenges.